Hypocholesterolemic and hypoglicemic effects of butyrylated arrowroot starch on Sprague Dawley rats - ., Damat; Marsono, Y.; ., Haryadi; Cahyanto, M. N. (Indonesian Journal of Pharmacy, 2008)
The aim of research is to investigate the hypocholesterolemic and hypoglicemic effects of butyrylated arrowroot starch in rat. The study was carried out using 30 Sprague Dawley rats which were divided into 5 groups of six rats. Each group was fed with different diets, i.e. diet containing butyrylated arrowroot starch with different degrees of substitution (DS of 0; 0.053; 0.120 and 0.187) and standard diet (AIN93). After 34 days feeding, the rats were killed and the blood was taken and analyzed for total cholesterol, triglyceride, LDL cholesterol, HDL cholesterol, and glucose concentrations. The result showed that rats fed with diet containing butyrylated arrowroot starch had lower concentration of total cholesterol, LDL cholesterol, glucose, and triglyceride, but the HDL cholesterol concentration was higher than those fed with arrowroot starch and standard diet AIN93. The higher the degree of substitution of the starch in the diet gave improved on those parameters. Butyrylated arrowroot starch has hypocholesterolemic and hypoglycemic effect.Key word: Butyrylated arrowroot starch, hypocholesterolemic, hypoglicemic